Implications of Financial Literacy, Lifestyle, and Social Factors on Student Financial Behavior - Irdiana, Sukma; Lukiana, Ninik; Kasim, Kasno T (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
Good financial literacy helps them make smart financial decisions, such as saving, investing and managing debt. This has a positive impact on long-term financial well-being, reducing the risk of getting into debt, and increasing the ability to achieve financial goals such as buying a home or starting a business. Apart from that, financial literacy also helps Generation Z understand the importance of planning for retirement early, as well as avoiding fraud and financial traps. In a broader context, a financially literate generation can also contribute to overall economic stability. This research aims to analyze the influence of financial literacy, lifestyle and social environment on students' financial behavior. The data used in this research is quantitative data collected through questionnaires distributed to students. The research method uses random sampling with a quantitative approach, and data collection techniques are carried out through questionnaires. This research involved 150 students as respondents. Data analysis was carried out using multiple linear regression. The research results showed that financial literacy, lifestyle and social environment had a positive and significant influence on students' financial behavior.